Diversity of juvenile decapods in Penor river estuaries in Pahang - Yusof, Muhammad Fitri; Mohd Radzi, Noor Najihah; Mohamed, Ahmad Azfar; Abdurahman, Siti Waznah (IIUM Journal Publication Unit, 2019)
Studies of decapods diversity are important to understand the species composition in a particular habitat. However, this information is very minute in Pahang estuaries area. This study was conducted to identify diversity and abundance of juvenile decapods in Penor River of Pahang. Specimens were collected from three different locations of the rivers using a traditional fish trap. The samples collected and identified into genus based on their morphological characteristics before analysed by using the Shannon-Wiener Diversity Index and Simpson’s Diversity Indices. The highest diversity of decapods found at Penor River at middle and inner rivermouth in the middle of the year respectively, while the lowest diversity of decapods recorded at this river is outer rivermouth in May. The result gives an impact on which months the decapods inhabit river estuaries.